KAJIAN GENDER PADA NOVEL KARYA NAWAL EL SAADAWI DAN SUTAN TAKDIR ALISJAHBANA - Ritonga, Deffi Syahfitri (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
The negative view about women was a result of sheer misunderstanding over religious teachings and cultural construction of gender bias. It became one of the major causes for women’s weak positions in both society and religion. The female figure was often misconstrued either in the pattern of her body or in her relation patterns with men. This article was expected to uncover the figure of a woman through the perspectives of two authors, male and female (authors), represented in literary works. The research method used descriptive qualitative comparative in which it revealed the texts referring to the views of both authors on women through feminist theory of literary criticism.DOI : 10.15408/a.v3i1.2976